G gamma beta + type of hereditary persistence of fetal haemoglobin in association with Hb C. - Higgs, D R (1979)
This report describes a Negro family with the G gamma beta + type of hereditary persistence of fetal haemoglobin. Family members with levels of haemoglobin F of 17 to 23% had normal red cell indices, balanced globin chain synthesis, and a pancellular distribution of the fetal haemoglobin, showing that these subjects have a form of HPFH. The production of Hb A and C in addition to the large amount of Hb F in one family member showed that there was an active beta A gene in cis to the HPFH determinant, while structural analysis of the Hb F revealed the presence of only G gamma chains. The criteria for the diagnosis of G gamma beta + HPFH, and the relevance of such conditions to the control of globin gene expression, are discussed.